(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
Even in the 1930s, the trend of unreasonably accelerating the pace of industrial construction continued in Uzbekistan. In the economy of the republic, the specialization of the country as the main cotton base was further strengthened.